2018
DOI: 10.1016/j.ijid.2018.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Rubella virus infections and immune status among pregnant women before the introduction of rubella vaccine in Amhara Regional State, Ethiopia

Abstract: A large number of pregnant women had acute/recent rubella virus infections at the time of data collection, indicating that the virus is endemic in the study area. More than a tenth of pregnant women were found to be susceptible to acquiring the infection in future pregnancies, with the possible risk of rubella-associated congenital anomalies. Hence screening of all women of child-bearing age before conception and during pregnancy might reduce the devastating effects of the virus on the developing fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
33
6
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(50 citation statements)
references
References 45 publications
9
33
6
2
Order By: Relevance
“…Also, the statistical analysis results showed the highly significant (P<0.05) differences between anti-rubella IgG prevalence and most of the educational level except individuals having a university degree. These findings are in agreement with Wang et al, 24,25 in Taiwan, that revealed that there was a statistically significant association between the low educational level and seronegativity to rubella. A similar study by Wondimeneh et al, 24 observed that no formal education participants had a slightly high rate of anti-rubella IgG.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Also, the statistical analysis results showed the highly significant (P<0.05) differences between anti-rubella IgG prevalence and most of the educational level except individuals having a university degree. These findings are in agreement with Wang et al, 24,25 in Taiwan, that revealed that there was a statistically significant association between the low educational level and seronegativity to rubella. A similar study by Wondimeneh et al, 24 observed that no formal education participants had a slightly high rate of anti-rubella IgG.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with Wang et al, 24,25 in Taiwan, that revealed that there was a statistically significant association between the low educational level and seronegativity to rubella. A similar study by Wondimeneh et al, 24 observed that no formal education participants had a slightly high rate of anti-rubella IgG. In Iraq, Al-Mukhtar et al, 23 recorded that the higher prevalence was among individuals with the education of diploma or college and illiterate while the lower rate was among the high school individual.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations